Development and characterization of human monoclonal antibodies that neutralize multiple TGFβ isoforms. Issue 2 (17th February 2016) - Bedinger, Daniel; Lao, Llewelyn; Khan, Shireen; Lee, Steve; Takeuchi, Toshihiko; Mirza, Amer M.
ABSTRACT: Transforming growth factor (TGF)β levels are elevated in, and drive the progression of, numerous disease states such as advanced metastatic cancer and systemic and ocular fibrosis. There are 3 main isoforms, TGFβ1, 2, and 3. As multiple TGFβ isoforms are involved in disease processes, maximal therapeutic efficacy may require neutralization of 2 or more of the TGFβ isoforms. Fully human antibody phage display libraries were used to discover a number of antibodies that bind and neutralize various combinations of TGFβ1, 2 or 3. The primary panning did not yield any uniformly potent pan-isoform neutralizing antibodies; therefore, an antibody that displayed potent TGFβ 1, 2 inhibition, but more modest affinity versus TGFβ3, was affinity matured by shuffling with a light chain sub-library and further screening. This process yielded a high affinity pan-isoform neutralizing clone. Antibodies were analyzed and compared by binding affinity, as well as receptor and epitope competition by surface plasmon resonance methods. The antibodies were also shown to neutralize TGFβ effects in vitro in 3 assays: 1) interleukin (IL)-4 induced HT-2 cell proliferation; 2) TGFβ-mediated IL-11 release by A549 cells; and 3) decreasing SMAD2 phosphorylation in Detroit 562 cells. The antibodies' potency in these in vitro assays correlated well with their isoform-specific affinities. Furthermore, the ability of the affinity-matured clone to decrease tumor burden in a Detroit 562 xenograft study was superior to that of the parent clone. This affinity-matured antibody acts as a very potent inhibitor of all 3 main isoforms of TGFβ and may have utility for therapeutic intervention in human disease.